Non-HDL Cholesterol And LDL-C/HDL-C Ratio In Type II Diabetic Patients - INDUMATI.V; VIDYA.S.PATIL; KRISHNASWAMY.D; SATISHKUMAR.D; VIJAY.V; MAHESH.S; RAJESHWARI.V (International Journal of Pharma and Bio Sciences, 2011)
Diabetic dyslipidemia consists of elevated LDL cholesterol, Triglycerides and decreased levels of HDL Cholesterol. More recent data suggests that measurement of Non -HDL Cholesterol level (calculated as Total Cholesterol minus HDL Cholesterol) could be more representative of all atherogenic, apolipoprotein (apo) B containing lipoproteins. Although apolipoprotein B can be assessed directly, measurement of Non-HDL Cholesterol can be considered as a surrogate marker for apolipoprotein B in routine clinical practice. Here an attempt is to evaluate the Lipid profile including Non-HDL Cholesterol levels and LDL-C/HDL-C ratio in type II Diabetic Patients as markers of diabetic dyslipidemia. Our study group comprised of age and sex matched 50 normal, 50 type II diabetic subjects. There was a significant increase in Non-HDL cholesterol (p<0.001) and LDL-C/HDL-C ratio(P<0.05) in diabetic patients compared to age and sex matched controls. Hence Non-HDL Cholesterol along with LDL-C/HDL-C ratio can be used as markers of dyslipidemia in Type II Diabetic patients.